Klasifikasi Cuaca di DKI Jakarta Menggunakan Metode Gaussian Naive Bayes - Raditama, Audi; Irwanto, Andhika Fariz; Majid, Yoga Fadillah Putra (Jurnal Riset Informatika dan Teknologi Informasi, 2023)
Weather Classification can help the community and related parties in making the right decisions, especially in planning daily activities. The Naïve Bayes method is used in this study because of its superiority in classifying data that has many attributes. The weather data used in this study includes variables such as humidity, degree Celsius temperature, weather. The naïve Bayes model is tested using test data for the accuracy of the model and evaluated by calculating the accuracy evaluation metric. Therefore, weather determination to obtain weather information needs to be made so that it can be utilized by the community. The results showed that the Gaussian Naïve Baiyes method could classify DKI Jakarta weather conditions with an accuracy of 81.25%. The results of this evaluation provide an overview of how good the Naïve Bayes model is in classifying DKI Jakarta weather